MPPT System Using Incremental Conductance for Solar Cell in Normal and Partial Shading Conditions - Pramudya Widyantoro; Rummi Sirait; Akhmad Musafa (IAES Indonesia Section, 2019)
In this research, MPPT (maximumpower point tracking) system has been created onsolar cells to get maximum power from solar cells.The designed system consists of 200 watt solar cells,voltage sensors, current sensors, microcontroller, DCDCconverter,andresistiveloads.TheMPPTsystem created uses incremental conductance algorithm toset the switching duty cycle on the DC-DC converter,with input parameters in the form of ΔV and ΔI toproduce maximum power. This system is tested onsolar cells with normal or partial shading conditionsand under conditions of shadow-covered solar cells of8%, 16%, 30%, 41% and 50% with a load of 10 Ohm,25 Ohm, and 35 Ohm. The results obtained that theMPPT system can stabilize the output power of solarcells both under normal and shadow conditions andare able to maintain output power when there is achange in input power with the maximum efficiencyof the MPPT system at a load of 10 Ohm of 78,38%with a standard deviation at the input power of 12,68and standard deviation at output power of 7,74.Maximum efficiency at 25 Ohm load of 80,23% withstandard deviation at input power of 3,59 andstandard deviation at output power of 2,90.Maximum efficiency at 35 Ohm load is 82,7% withstandard deviation at input power of 4,14 andstandard deviation at output power of 3,29.